Sexual Violence as a Weapon of War? Perceptions, Prescriptions, Problems in the Congo and Beyond - Eriksson Baaz, Maria (Africa Now, 2013)
All too often in conflict situations, rape is referred to as a 'weapon of war', a term presented as self-explanatory through its implied storyline of gender and warring. In this provocative but much-needed book, Eriksson Baaz and Stern challenge the dominant understandings of sexual violence in conflict and post-conflict settings. Reading with and against feminist analyses of the interconnections between gender, warring, violence and militarization, the authors address many of the thorny issues inherent in the arrival of sexual violence on the global security agenda. Based on original fieldwork in the Democratic Republic of the Congo, as well as research material from other conflict zones, Sexual Violence as a Weapon of War? challenges the recent prominence given to sexual violence, bravely highlighting various problems with isolating sexual violence from other violence in war. A much-anticipated book by two acknowledged experts in the field, on an issue that has become an increasingly important security, legal and gender topic.